Stimulators of tumour necrosis factor production released by damaged erythrocytes. - Bate, C; Kwiatkowski, D (1994)
We sought to characterize factors released by sonicated human erythrocytes that stimulate peripheral blood mononuclear cells (PBMC) to release tumour necrosis factor-alpha (TNF). This response is not inhibited by polymyxin B, indicating that contaminating lipopolysaccharide (LPS) is not responsible. When erythrocyte lysates are fractionated by reverse-phase chromatography using a gradient of n-propanol on Sep-Pak C18 cartridges, the TNF-inducing activity elutes as a single peak. The erythrocyte-derived TNF-inducing activity is unaffected by digestion with proteases but is destroyed by mild base hydrolysis or digestion by lipases, indicating that compounds containing ester-linked acyl chains may be essential. These properties are similar to those of TNF stimulators that we have previously identified in erythrocytes infected with malaria parasites, except that the TNF-inducing activity per cell is about 200 times higher in parasitized erythrocytes than in uninfected erythrocytes. Lipase-digested erythrocyte lysates inhibit the TNF-inducing factors of both normal and malaria-infected erythrocytes, suggesting that lipase digestion creates partial structures which compete with active components for macrophage receptors. Such receptors may recognize a common structure that contains an inositol monophosphate (IMP)-like component, as IMP also inhibits the TNF response to erythrocyte-derived factors and to parasite lysates whereas it does not affect the response to LPS. We conclude that lysed erythrocytes release specific cytokine-inducing factors that may contribute to the fever response to non-infectious tissue injury.